2005
DOI: 10.1007/s00122-005-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of a new brown planthopper (BPH) resistance gene, Bph18(t), and marker-assisted selection for BPH resistance in rice (Oryza sativa L.)

Abstract: Brown planthopper (BPH) is a destructive insect pest of rice in Asia. Identification and the incorporation of new BPH resistance genes into modern rice cultivars are important breeding strategies to control the damage caused by new biotypes of BPH. In this study, a major resistance gene, Bph18(t), has been identified in an introgression line (IR65482-7-216-1-2) that has inherited the gene from the wild species Oryza australiensis. Genetic analysis revealed the dominant nature of the Bph18(t) gene and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
139
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 20 publications
0
139
0
7
Order By: Relevance
“…On the basis of our results and knowledge currently available about BPH-resistance genes on chromosome 12L, we propose that allelotype BPH1/9-1 (including previously reported BPH1, BPH10, BPH18, and BPH21) evolved early in the wild progenitor of rice based on two lines of evidence. First, BPH10 and BPH18 were introgressed from the wild rice species O. australiensis (E genome) (29,42) and BPH21 from O. minuta (BC genome) (30), respectively. Second, the allelotype BPH1/9-1 (H20) was found to be the most widespread among the four resistant allelotypes in rice populations (SI Appendix, Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of our results and knowledge currently available about BPH-resistance genes on chromosome 12L, we propose that allelotype BPH1/9-1 (including previously reported BPH1, BPH10, BPH18, and BPH21) evolved early in the wild progenitor of rice based on two lines of evidence. First, BPH10 and BPH18 were introgressed from the wild rice species O. australiensis (E genome) (29,42) and BPH21 from O. minuta (BC genome) (30), respectively. Second, the allelotype BPH1/9-1 (H20) was found to be the most widespread among the four resistant allelotypes in rice populations (SI Appendix, Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…S14B; refs. [26][27][28][29][30]. Thus, our findings demonstrated that the eight genes in this cluster are multiple alleles of the same locus, and, to honor the priority in the literature, we designate this locus BPH1/9.…”
Section: Bph9 Encodes An Endomembrane-localized Nucleotide-binding Andmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous results have been reported that brown planthopper is a destructive phloem sap sucking pest of rice which has negative effect both qualitative and quantitative (Jena et al 2006). In this study, we searched for hybrid lines having resistant genes for brown plant hopper, namely, Bph1, Bph18(t), and Wbph in 173 hybrid rice lines.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2005) and Jena et al (2006) revealed that RM8213 and RM5953 DNA markers are closely linked to Bph17 gene that controls the expression of resistance trait. These markers can be used as a tool of marker assisted selection (MAS) with marker alleles at 177 bp on RM8213 PCR products and 140 bp on RM5953 PCR products (Sun et al 2005;Jena et al 2006). DNA products of RM8213 follow the Mendelian inheritance pattern of 1:2:1 (susceptible: heterozygous segregation: resistant) (Pertiwi et al 2014;Carsono et al 2016).…”
Section: Introductionmentioning
confidence: 99%